Blood parameters and productivity of broilers fed ration composed of microparticle protein with the addition of Lactobacillus sp. - Wulandari, L.T.; Suthama, N.; Sukamto, B. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The study was aimed to evaluate the effectiveness of feeding dietary microparticles protein added with Lactobacillus sp. on blood parameters and broiler productivity. A total of 192 birds of 21 days old broiler with initial body weight of 481 ± 67 g were divided into 8 treatments and 4 replications (6 birds each) of a completely randomized design (CRD). Dietary treatments were T0: 21% intact protein ration, T1: 18% intact protein ration, T2: 21% microparticle protein ration, T3: 18% microparticle protein ration, T4: T0 + 1.2 mL Lactobacillus sp, T5: T1 + 1.2 mL Lactobacillus sp., T6: T2 + 1.2 mL Lactobacillus sp., and T7: T3 + 1.2 mL Lactobacillus sp. Parameters observed were total lactic acid bacteria and Coliform, pH, blood cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), meat cholesterol, meat weight, feed consumption, and body weight gain (BWG). Data were analyzed using analysis of variance and followed by Duncan test (P<0.05). The results showed that T7 treatment significantly (P<0.05) decreased blood cholesterol, LDL, and meat cholesterol, but increased HDL, meat weight, and BWG. Blood cholesterol, LDL, and meat cholesterol were indicated significantly (P<0.05) lowest values due to T7 treatment. In conclusion, feeding 18% microparticle protein with addition of 1.2 mL Lactobacillus sp. can improves blood status and increases broiler productivity.